Design and evaluation of fluorescent and non-fluorescent bivalent ligands to explore their mode of action at neuropeptide Y receptors - Richardson, Rachel (2019)
Recent advances in understanding G protein coupled receptor (GPCR) pharmacology include accumulating evidence that GPCRs can form homo- and hetero- meric complexes, and that these complexes may affect physiological function and ligand pharmacology. However, the continuing controversy over the significance of such complexes has arisen, in part, due to a limited availability of appropriate molecular tools and ligands that would allow for a more comprehensive investigation of oligomer pharmacology. One avenue to exploit dimer selective pharmacology has been the development of bivalent ligands. However, a number of mechanisms, not all of which involve receptor dimerization, can often explain the properties of bivalent compounds.